Pengembangan Skill Assesment Keamanan Jaringan - Rochmad Mohammad Thohir Yassin; Alfian Zakaria (Jurnal Teknik, 2020)
The development of Information and Communications Technology (ICT) also influences the education sector, ICT is encouraged to be able to support education as a medium that is quite effective to accommodate interaction between lecturers/teachers and students without the limits of space and time. The purpose of this research is to develop skills assessment using simulation software and to improve student understanding of each lecture material as well as student competency in the field of network security. The method used in this research is the experimental method. The results of the research are the development of learning media in the form of skills assessment and the prototype of a mobile-based learning application to measure learning achievement in the field of network security.